Uma função afim f é tal que f(-1)=3 e f(1)=1 Determine o valor de

Uma função afim f é tal que f(-1)=3 e f(1)=1 Determine o valor de



  • Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
    f(x) = ax + b

    -a + b = 3
    a + b = 1
    2b = 4
    b = 2



    a = 1 — b
    a = 1- 2
    a = — 1

    F(x) = — 1x + 2

    ==================================================

    F(3) = -1(3) + 2 = — 3 + 2 ==> F(3) = — 1

  • Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
    Ol
    Resolvendo temos:

    uma funao assim: f(x)=mx+b ………baseado nesa condiao resolvemos:

    Resolvendo : f(-1)=3

    f(-1)=3 pela condiao da funao temos:
    f(-1)=3 => f(-1)=m(-1)+b
    3=-m+b
    b-m=3……………..(I) equaao
    ——————————————————————————————
    agora resolvendo : f(1)=1
    f(1)=1=>f(1)=m.1+b
    1=b+m
    b+m=1………………….(II) equaao
    —————————————————————————————
    somamos equaao (I)+(II) assim:
    b-m=3
    b+m=1
    ——————-
    2b =4
    b=2………….achamos o valor de (b)
    —————————————————————————————
    agora para achar (m) s substituir na equaao (I) ou (II) opcional.
    eu vou substituir na equaao (II) veja

    b+m=1………b=2
    2+m=1
    m=1-2
    m=-1……………achamos o valor de(m)
    —————————————————————————————
    agora vamos resolver f(3)

    f(3)=f(x)=m.x+b
    f(3)=m.3+b
    f(3)=3m+b…………..ja temos os valores de (m=-1) e b=2 .susbtituindo
    f(3)=3.(-1)+2
    f(3)=-3+2
    f(3)=-1———>Resposta
    ================================================
    Espero ter ajudado!!


Добавить комментарий

8 + 2 =